Atomic-level organization of vicinal acid–base pairs through the chemisorption of aniline and derivatives onto mesoporous SBA15. Issue 9 (16th June 2016) - Hamzaoui, Bilel; Bendjeriou-Sedjerari, Anissa; Pump, Eva; Abou-Hamad, Edy; Sougrat, Rachid; Gurinov, Andrei; Huang, Kuo-Wei; Gajan, David; Lesage, Anne; Emsley, Lyndon; Basset, Jean-Marie
Abstract : The design of novel heterogeneous catalysts with multiple adjacent functionalities is of high interest to heterogeneous catalysis. Abstract : The design of novel heterogeneous catalysts with multiple adjacent functionalities is of high interest to heterogeneous catalysis. Herein, we report a method to obtain a majority of bifunctional acid–base pairs on SBA15. Aniline reacts with SBA15 by opening siloxane bridges leading to N -phenylsilanamine–silanol pairs. In contrast with ammonia treated surfaces, the material is stable under air/moisture. Advanced solid state MAS NMR (2D 1 H– 1 H double-quantum, 1 H– 13 C HETCOR) experiments and dynamic nuclear polarization enhanced 29 Si and 15 N spectra demonstrate both the close proximity between the two moieties and the formation of a covalent Si–N surface bond and confirm the design of vicinal acid–base pairs. This approach was successfully applied to the design of a series of aniline derivatives of bifunctional SBA15. A correlation between the substituent effects on the aromatic ring (Hammett parameters) with the kinetics of a model Knoevenagel reaction is observed.